2012
DOI: 10.1063/1.4734510
|View full text |Cite
|
Sign up to set email alerts
|

Negative refraction and partial focusing with a crossed wire mesh: Physical insights and experimental verification

Abstract: We experimentally verify that a flat metamaterial lens formed by nonconnected crossed metallic wires enables the partial focusing of electromagnetic waves, as a consequence of the phenomenon of all-angle broadband negative refraction in such media. We prove that the strength of the negative refraction effect can be controlled by adjusting the angle between the crossed wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…At microwave frequencies wire media as an artificial material has been known for a long time [1], [2], and it has gained attention in the last two decades in metamaterials research ranging from microwaves to optics in relation to observed anomalous wave phenomena such as negative refraction [3]- [9], canalization, transport, and magnification of the near field to distances of several wavelengths [10]- [14], subwavelength imaging of the near field [15]- [22], and radiative heat transfer [23]- [25]. A broad range of applications of wire-media metamaterials at terahertz (THz) and optical frequencies is given in [26].…”
Section: Introductionmentioning
confidence: 99%
“…At microwave frequencies wire media as an artificial material has been known for a long time [1], [2], and it has gained attention in the last two decades in metamaterials research ranging from microwaves to optics in relation to observed anomalous wave phenomena such as negative refraction [3]- [9], canalization, transport, and magnification of the near field to distances of several wavelengths [10]- [14], subwavelength imaging of the near field [15]- [22], and radiative heat transfer [23]- [25]. A broad range of applications of wire-media metamaterials at terahertz (THz) and optical frequencies is given in [26].…”
Section: Introductionmentioning
confidence: 99%
“…in [18]). Electromagnetic properties of these structures have a number of common features with hyperbolic materials (enhancement of radiation from small sources, negative refraction at interfaces [19,20], etc), although wave-guiding media are formed by ordinary metals and dielectrics, and, moreover, due to their strongly spatially dispersive nature, cannot be described by a local permittivity tensor. Realizations of wave-guiding media do not necessarily require exotic materials with negative and positive permittivities.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that a simple periodical array of PEC strips to some extent behaves similarly to hyperbolic materials and can offer a variety of means to control electromagnetic waves with flexibility and robustness. In contrast to earlier studies of tilted wire-medium slabs [19,20], which are based on corresponding homogenized models, we consider the actual TEM waveguides formed between the PEC strips. where the used Cartesian coordinate system ( )…”
Section: Introductionmentioning
confidence: 99%
“…Such engineered structures have yielded an 'effective' electromagnetic response that is normally not encountered in nature. Aside from enabling these new frontiers and interesting scientific properties such as a negative index of refraction, 10,11 negative refraction, 12 indefinite media 13 or nearfield imaging, 11,14 MTMs have shown to be beneficial for various existing applications. For instance, MTMs show superior performance over prior techniques for absorption, wave guidance and narrowband emission of light for solar and/or thermal photovoltaic cell applications.…”
Section: Introductionmentioning
confidence: 99%